2015
DOI: 10.1097/opx.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Aniseikonia Induced by Cataract Surgery and Its Effect on Binocular Vision

Abstract: Aniseikonia induced by cataract surgery may not be a substantial problem for ametropic adults with normal binocular vision, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
1
29
0
4
Order By: Relevance
“…However, Rutstein et al. () used the same methodology as Kramer et al. and did not find any correlation between aniseikonia specific symptoms and anisometropia in a prospective study of patients undergoing bilateral cataract operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rutstein et al. () used the same methodology as Kramer et al. and did not find any correlation between aniseikonia specific symptoms and anisometropia in a prospective study of patients undergoing bilateral cataract operation.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that 9/10 symptoms decreased from preoperative to in between surgeries where the anisometropia was most pronounced (Rutstein et al. ). Moreover, we did not find any correlation between aniseikonia and PRO (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The goals of this study were to validate a new stereopsis test for iPad and to assess its reproducibility in comparison with TNO at near and HD at distance. The stereopsis at near is widely used in clinical practice in order to improve paediatric vision screening programs, to provide an overall indication of binocularity, and to monitor binocularity after vision therapy or after monovision (Fricke et al 1997;Rutstein et al 2015). On the other hand, the measurement of distance stereopsis is uncommon in clinical practice even though it has been suggested that may be more effective than near stereopsis testing in screening for binocular vision disorders, reduced visual acuity, and uncorrected refractive errors (Rutstein and Corliss 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One of the strengths of ST is the possibility to measure stereopsis at multiple distances maintaining the same sensitivity of stereoacuity. This makes the app especially useful to measure stereopsis at near, intermediate and distance vision with multifocal contact lenses or after cataract surgery with multifocal refractive intraocular lenses (Rutstein et al 2015), even though an understimation with diffractive intraocular lenses might be found due to be a wavelength-based stereotest (Varón et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although much research was conducted from the mid‐1930s to the 1980s, aniseikonia has largely been ignored in clinical practice. Recently, there has been a renaissance of aniseikonia research following advancements in multifocal lens designs in cataract surgery, retinal surgeries such as epiretinal membrane peels, and refractive surgeries, which have resulted in an increase in the number of reported cases …”
mentioning
confidence: 99%